EVALUASI IMPLEMENTASI KURIKULUM 2013 DI MADRASAH - Sumarni, Sumarni (Badan Litbang dan Diklat Kementerian Agama RI, 2017)
AbstractThe Ministry of Religion in 2014 conducted apilot implementation of the 2013 curriculum for thesubjects of Islamic Education and Arabic. This studyfocuses on the policy of implementation and implementation of Curriculum 2013 in Madrasah Aliyah (MA) of West Java. This study uses quantitativeapproach. The research subjects were madrasahhead, teacher, learner, supervisor, and madrasahcommittee. The instruments used were questionnaires, interview guides, and documentation. Thedata was analyzed using quantitative descriptivetechnique. The results show that most respondentsunderstand the purpose of the implemented curriculum 2013 and the scientifc approach used. Inthe implementation of the 2013 curriculum, mostof the respondents also stated that PAI teachersalready have the ability to learn in the 2013 curriculum. The 2013 Curriculum Implementationalso has a positive impact for students, teachersand Madrasah Aliyah. Nevertheless, there are stillsome problems that arise related to infrastructure,teacher training, teacher and student handbooks,and the absence of monitoring and evaluationmonitoring from the government towards the implementation of Curriculum 2013.Â AbstrakKementerian Agama pada tahun 2014melakukan uji coba implementasi kurikulumm2013 untuk mata pelajaran Pendidikan AgamaIslam dan Bahasa Arab. Studi ini memfokuskanpada kebijakan implementasi dan penelahaanterhadap implementasi Kurikulum 2013 diMadrasah Aliyah (MA) wilayah Jawa Barat.Penelitian ini menggunakan pendekatankuantitatif. Subjek penelitian adalah kepalamadrasah, guru, peserta didik, pengawas, dankomite madrasah. Instrumen yang digunakanyaitu lembar angket, pedoman wawancara,dan dokumentasi. Analisis data menggunakanteknik deskriptif kuantitatif. Hasil penelitianmenunjukkan bahwa sebagian besar respondenmemahami tujuan dari diimplementasikankurikulum 2013 dan pendekatan saintifk yangdigunakan. Dalam implementasi kurikulum 2013,sebagian besar responden juga menyatakan yakinbahwa para guru PAI sudah memiliki kemampuandalam pembelajaran dengan kurikulum 2013.Implementasi Kurikulum 2013 juga memilikidampak positif baik bagi peserta didik, guru, danKepala MA. Namun demikian masih ada beberapapermasalahan yang muncul terkait dengan saranaprasarana, pelatihan guru, buku pegangan untukguru dan siswa, serta tidak adanya evaluasi danmonitoring monitoring dari pemerintah terhadapimplemntasi Kurikulum 2013.